Epistemologi Etika Lingkungan dalam Filsafat Islam: Aplikasi pada Pendidikan Karakter Siswa Madrasah Ibtidaiyah (MIS Hamalatul Qur’an) - Pitriatin, Pitriatin; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2026)
The global environmental crisis and the low ecological awareness among Muslim students require the strengthening of character education based on environmental ethics from the perspective of Islamic philosophy. By using a case study that focuses on the character education of Madrasah Ibtidaiyah (MI) students, this paper investigates the epistemology of environmental ethics in Islamic philosophy. This study aims to analyze how the concept of Islamic epistemology based on wahyu (revelation), akal (reason), and experience shapes environmental ethics as part of the amanah (trust) of humans as khalifah (vicegerent) of Allah on earth. Using a qualitative case study approach at MIS Hamalatul Qur’an, Karawang, the data were collected through participant observation, in-depth interviews, and document analysis for three months, then analyzed descriptively. The results show that the integration of Islamic values such as khilafah (caliphate) and amanah into the character education curriculum can increase students’ environmental awareness and encourage behavioral changes toward more responsible behavior, for example reducing the habit of littering. Nevertheless, implementation challenges such as limited resources need to be addressed to ensure the sustainability of the program. This paper contributes to the development of Islamic Religious Education (PAI) by providing practical recommendations for teachers and madrasah administrators, while at the same time filling the research gap related to the epistemology of environmental ethics at the elementary education level.